Comparison of the mitochondrial genomes of the Old and New World strains of the legume pod borer, Maruca vitrata (Lepidoptera: Crambidae). (17th August 2017) - Agunbiade, Tolulope A.; Coates, Brad S.; Sun, Weilin; Tsai, Mu-Rou; Valero, Maria Carmen; Tamò, Manuele; Pittendrigh, Barry R.
Abstract: Maruca vitrata (Fabricius, 1787) is a cryptic pantropical species of Lepidoptera that are comprised of two unique strains that inhabit the American continents (New World strain) and regions spanning from Africa through to Southeast Asia and Northern Australia (Old World strain). In this study, we de novo assembled the complete mitochondrial genome sequence of the New World legume pod borer, M. vitrata, from shotgun sequence data generated on an Illumina HiSeq 2000. Phylogenomic comparisons were made with other previously published mitochondrial genome sequences from crambid moths, including the Old World strain of M . vitrata . The 15, 385 bp M. vitrata (New World) sequence has an 80.7% A+T content and encodes the 13 protein-coding, 2 ribosomal RNA and 22 transfer RNA genes in the typical orientation and arrangement of lepidopteran mitochondrial DNAs. Mitochondrial genome-wide comparison between the New and Old World strains of M. vitrata detected 476 polymorphic sites (4.23% nucleotide divergence) with an excess of synonymous substitution as a result of purifying selection. Furthermore, this level of sequence variation suggests that these strains diverged from ~1.83 to 2.12 million years ago, assuming a linear rate of short-term substitution. The de novo assemblies of mitochondrial genomes from next-generation sequencing (NGS) reads provide readily available data for similar comparative studies.